Revisiting the Ethics of Circumvention Tourism. Issue 3 (2022) - Snyder, Jeremy C.
Abstract : In the context of medical tourism, circumvention tourism consists of traveling abroad with the intention of participating in a health-related activity that is prohibited in one's own country but not in the destination country. This practice raises a host of legal and ethical questions that focus on how the traveler should be treated once they have returned home. Joshua Shaw 1 deftly shows that the question of whether circumvention tourists should be punished in their home countries is not something that can be answered in principle and without reference to the prima facie morality of the prohibition. This implicates formalist accounts of circumvention tourism developed by Pennings 2 and Huxtable 3 that argue against punishing travelers who access fertility treatments and medical assistance in dying abroad on the grounds that civic peace and stability require opportunities for individuals to travel internationally to access domestically prohibited medical services.